Investigating Students’ Creativity through STEM-Engineering Design Process in Element, Compound, and Mixture Topic - Fajarwati, Andini; Winarno, Nanang; Prima, Eka Cahya (Indonesian Journal of Teaching in Science, 2024)
The STEM-Engineering Design Process is one of the learning models that encourage students to do engineering activities to solve real-life problems. This study aims to investigate the effect of the STEM-Engineering Design Process on students’ creativity in element compound, and mixture topics. A quasi-experimental design is used in this study. The implementation of the STEM-engineering design process was conducted in the experiment class, while the control class carried out conventional learning. Both classes are making water filtration tools. Purposive technique sampling was carried out to choose the sample with a certain category of 9th-grade students in one of the private schools in Bandung, West Java, Indonesia. Students ranged in age from 14-15 years old and were divided into experiment and control classes. Each class has 19 students. This research uses a creativity questionnaire Likert scale to collect the data. The result of this study showed there is no significant difference in students’ creativity between experiment and control class. The N-Gain scores in the experiment and control class are 0.06 and 0.03 which are described as low. Even though the gain is low, there is still a difference between the experiment and control class in the favour of experiment class. The STEM-engineering design process has a positive impact on creativity in learning element compounds and mixtures.